Pembentukan Sistem Dispersi Padat Amorf Azitromisin Dihidrat dengan Hikroksipropil Metilselulosa (HPMC) - Erizal Zaini; Netty Novitasari; Maria Dona Octavia (Fakultas Farmasi Universitas Andalas, 2017)
The aim of present study is to develop solid dispersion system of azithromycin dihydrate with hydroxypropyl methylcellulose E5 LV (HPMC) for improving the dissolution rate of azithromycin dihydrate. Amorphous solid dispersions were prepared by solvent method at 1:1; 1:2 and 2:1 (w/w) drug to polymer ratios. Solid state properties of amorphous solid dispersion were evaluated by X-ray powder diffraction (XRPD), scanning electron microscopy and spectroscopy FT-IR. Furthermore, the dissolution rate profile was investigated by type II USP dissolution apparatus. Based on X-ray powder diffractometry analysis, azithromycin dihydrate was transformed partially from the crystalline phase to the amorphous state as confirmed by significant reduction of the crystalline peaks intensity. FT-IR spectroscopy analysis revealed the absence of chemical interaction between azithromycin dihydrate and HPMC. The dissolution rate of azithromycin dihydrate from amorphous solid dispersion was substantially higher than azithromycin dihydrate intact and its physical mixture. The dissolution rate of azithromycin dihydrate increased with an increasing drug to polymer ratio.